A numerical approach to understand the responses of passenger vehicles moving through floodwaters - Al-Qadami, E.H.H. (John Wiley and Sons Inc, 2022)
Watercourses and roadways commonly intersect in their layout at many locations through bridges, drainages, and fords. During heavy rain events, watercourses may overflow causing serious disturbance toward traffic movement. Under such circumstances, attempting to drive through these intersections can be extremely dangerous. Therefore, understanding the responses of the vehicles moving through floodwaters is of utmost importance. Between 1967 and 2021, several studies have been published investigating the stability of static flooded vehicles. However, studies on the stability of vehicles in the movement are not sufficient at which only few experimental studies were published. Herein, for the very first time numerical simulations were conducted to investigate the hydrodynamic forces on a full-scale medium-size passenger vehicle moving perpendicular to the incoming floodwaters. Sliding and floating instability modes were observed by detecting the position of the vehicle centre of mass at each time step. Further, horizontal (FH) and vertical (FV) forces were measured and plotted against the governing flow parameters. Finally, it was observed that the critical flow depth was 0.38 m, while the minimum (Formula presented.) threshold function was 0.39 m2/s, for the tested vehicle. Later, a comparison between simulation outcomes and previously published experimental work was performed and a good agreement was observed. Â© 2022 Prince Sultan University. Journal of Flood Risk Management published by Chartered Institution of Water and Environmental Management and John Wiley & Sons Ltd.